ApoE Genotype, Lipid Profile, Exercise, and the Associations With Cardiovascular Morbidity and 18-Year Mortality. (4th October 2019) - Dankner, Rachel; Ben Avraham, Sivan; Harats, Dror; Chetrit, Angela
Abstract: Background: Studies of longevity examined apolipoprotein E (ApoE), a gene involved in lipoprotein metabolism, which interacts with susceptibility to age-related diseases, and with mortality. We evaluated the association of ApoE isoforms with cardiovascular disease (CVD) and all-cause mortality. Methods: A prospective cohort of 949 survivors of the Israel Study of Glucose Intolerance, Obesity, and Hypertension, examined during 1999–2004, mean age 72 years, was followed for mortality until 2017. Participants were interviewed for lifestyle habits and medical history. Anthropometrics and biochemical markers were taken. Logistic regression was used to assess CVD morbidity and Cox proportional hazard model for mortality. Results: The most common genotype in the cohort was ApoE E3 (76.3%), with the other two almost equally distributed (ApoE E2 11.2% and ApoE E4 12.5%). In men only, ApoE E4 associated with CVD (adjusted odds ratio = 1.46, 95% confidence interval [CI] 0.76, 2.80) and with 18-year mortality (adjusted hazard ratio = 1.47, 95% CI 0.95, 2.26), adjusting for age, ethnicity, physical activity, hypertension, diabetes, low-density lipoprotein (LDL)-cholesterol, high-density lipoprotein (HDL)-cholesterol, triglycerides and lipid-lowering medications. Low levels of HDL cholesterol, adjusted for ApoE and the above-mentioned variables, associated with higher prevalence of CVD (adjusted odds ratio = 1.35, 95% CI 1.00, 1.83) and all-cause mortality (adjusted hazard ratio = 1.42, 95% CI 1.14, 1.78). ApoE E3 and E2 conferred a lower 18-year mortality risk in the physically active individuals, compared to the sedentary (adjusted hazard ratio = 0.57, 95% CI 0.44, 0.74, and adjusted hazard ratio = 0.53, 95% CI 0.78, 1.02, respectively). Conclusions: In community-dwelling older adults, sociodemographic characteristics and physical activity, blood pressure and HDL-cholesterol levels, may outweigh the impact of ApoE polymorphisms on CVD morbidity and all-cause mortality.